2015
DOI: 10.1007/s00586-015-3851-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of tuberculosis and metastatic cancer in the spine using dynamic contrast-enhanced MRI

Abstract: Purpose To investigate the differences between imaging features of spinal tuberculosis (TB) and metastatic cancer measured by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). The presentation of TB on convention MRI may not show the typical TB signs, and they may be mis-diagnosed as malignant diseases. DCE-MRI may provide additional information to help making differential diagnosis. Materials and methods DCE-MRI was performed in 24 TB and 22 metastatic cancer patients. The DCE kinetic pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…DCEMRI using heuristic analysis and model fitting has been applied to characterize vascular properties of different hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement (8,9,15). We have shown that DCE parameters of metastatic cancers were significantly different from those of myeloma (10) and inflammatory TB (11). Unfortunately, there were few studies in the literature that reported the diagnosis of spinal masses using DCE-MRI for comparison with our findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DCEMRI using heuristic analysis and model fitting has been applied to characterize vascular properties of different hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement (8,9,15). We have shown that DCE parameters of metastatic cancers were significantly different from those of myeloma (10) and inflammatory TB (11). Unfortunately, there were few studies in the literature that reported the diagnosis of spinal masses using DCE-MRI for comparison with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…DCE-MRI has been applied to diagnose different spinal lesions (811) and distinguish between hypervascular (eg, renal cell carcinoma) and hypovascular (eg, prostate cancer) metastases (12,13). It has also been used to characterize vascular properties of hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement, as well as to evaluate changes after various therapies for predicting treatment outcome and prognosis (8,9,1420).…”
Section: Introductionmentioning
confidence: 99%
“…or the pharmacokinetic parameters K trans and k ep ; as well as for classification of the DCE kinetics into "wash-out," "plateau," or "persistent enhancement" pattern. 6,7 The DCE kinetic pattern was significantly different between GCT and chordoma. Consistent with a much higher proportion of GCT cases showed the early peak enhancement with the wash-out DCE pattern, the obtained pharmacokinetic parameters K trans and k ep were also much higher in GCT than in chordoma.…”
Section: Discussionmentioning
confidence: 98%
“…or the pharmacokinetic parameters K trans and k ep ; as well as for classification of the DCE kinetics into “wash-out,” “plateau,” or “persistent enhancement” pattern. 6,7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation